Anti-dazzle hardened film for surface of display screen and preparation method and application of anti-dazzle hardened film
By using modified micron-sized and nano-sized silica particles and nano-sized alumina particles, combined with the ratio design of acrylate oligomers and monomers, the problem of anti-glare and hard film hardness for vehicle-mounted displays in the existing technology is solved. , the problem of insufficient clarity and wear resistance, an efficient and economical anti-glare hard coating with high definition, high hardness and high wear resistance has been achieved.
Patent Information
- Application Number
- CN202411600170.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-01-21
AI Technical Summary
The prior art is difficult to provide high hardness, high definition and high wear resistance for automotive displays. The anti-glare and dura mater produced by domestic manufacturers is low in fineness and cannot meet the needs of automotive display screens.
Using micron-sized and nano-sized silica particles modified by silane coupling agents, as well as nano-sized alumina particles, and rationally designing the ratio of acrylate oligomers and acrylate monomers to form a high cross-linking density hardened layer to improve the hardness and wear resistance of the anti-glare film.
An anti-glare hard film with high definition, high hardness and high wear resistance is achieved, which is suitable for vehicle-mounted displays, improving the anti-glare performance and service life of the display while reducing manufacturing costs.
Smart Images

Figure BDA0005128070600000091 
Figure BDA0005128070600000101
Abstract
Description
Technical Field
[0001] The invention relates to an anti-glare hard film, in particular to an anti-glare hard film for a display screen surface and a preparation method and application thereof. Background Art
[0002] In recent years, with the rapid development of new energy vehicles, the per capita car ownership in Chinese families has also increased rapidly, and driving has become more and more common. At the same time, many in-vehicle display devices, such as in-vehicle navigation systems, have also brought a lot of comfort and convenience to people's travel. However, in the process of using these in-vehicle devices, they are inevitably affected by "glare", which can cause visual interference to drivers and passengers, affecting the driving experience at the least and causing traffic accidents at the worst. Therefore, anti-glare treatment is generally performed on the surface of various in-vehicle display screens to reduce the impact of glare.
[0003] At present, automobile manufacturers often stick high-hardness anti-glare and hard films inside or outside of vehicle-mounted display devices to solve the anti-glare problem of the screen. However, the high-precision anti-glare and hard films used in vehicles on the domestic market mainly come from Japan, among which DNP and Daicel Corporation occupy an absolute market share. This type of anti-glare and hard film is expensive and has a long supply cycle.
[0004] At present, the high-hardness anti-glare and hard-coated films produced by domestic manufacturers have low fineness and poor clarity. For example, the Chinese invention patent application with patent number CN202111661125.5 (publication number CN116410508A) discloses "A high-hardness anti-glare film and its preparation method", which uses a compound of silica particles with an average particle size of 4.2 to 5.2 μm and alumina particles with an average particle size of 300 nm to reduce the flash point. Although the surface hardness reaches 3H (JIS 5400), the compatibility of micron-scale silica particles and micro-nano-scale alumina particles is poor, and alumina particles are prone to self-agglomeration, resulting in low gloss and insufficient surface fineness. It can only be used for large conference display screens but not for vehicle-mounted display screens. Among the currently disclosed anti-glare and hard-coated film patents, few have the properties of high hardness, high clarity, and high wear resistance.
[0005] Therefore, it is necessary to design an anti-glare hard film for vehicle-mounted displays with high clarity, high hardness and high wear resistance to meet the downstream customers' requirements for the performance of hard film products and the manufacturing cost requirements of vehicle-mounted display touch screens. Summary of the invention
[0006] The first technical problem to be solved by the present invention is to provide an anti-glare hardened film for the surface of a display screen with high definition, high hardness and high wear resistance in view of the current status of the prior art.
[0007] The second technical problem to be solved by the present invention is to provide a method for preparing the above-mentioned anti-glare hard film in view of the current status of the prior art.
[0008] The third technical problem to be solved by the present invention is to provide an application of the above-mentioned anti-glare hard film in view of the current status of the prior art.
[0009] The technical solution adopted by the present invention to solve the above-mentioned first technical problem is: an anti-glare hard film for the surface of a display screen, comprising a substrate layer and a glue layer coated on the substrate layer, characterized in that the glue layer comprises the following components:
[0010] Acrylate oligomer 30.4-41.5%;
[0011] Acrylate monomer 4.6-6.3%;
[0012] Photoinitiator 2.0-3.0%;
[0013] Leveling agent 1.0~2.0%;
[0014] Dispersing aid 0.5-1.0%;
[0015] Main anti-glare particles 1.2% to 3.6%;
[0016] Auxiliary anti-glare particles 0.2-0.4%;
[0017] Hardened particles 10.4-31.1%;
[0018] Organic solvent 26.8~44.8%;
[0019] The contents of the above components are in percentage by weight;
[0020] The main anti-glare particles are micron-sized silicon dioxide particles modified by a silane coupling agent, the auxiliary anti-glare particles are nano-sized silicon dioxide particles modified by a silane coupling agent, and the hardening particles are nano-sized aluminum oxide particles.
[0021] The average particle size of the main anti-glare particles is 1.3 to 2.9 μm, the average particle size of the auxiliary anti-glare particles is 85 to 140 nm, and the average particle size of the hardened particles is 5 to 20 nm.
[0022] The anti-glare hard film provided by the present invention preferably has a haze range of about 4 to 15%, so as to ensure that it can provide a certain anti-glare performance in the actual application of the vehicle-mounted central control display outer screen, while not affecting the overall clarity and brightness of the display screen. When the haze is lower than 4%, the anti-glare hard film cannot provide sufficient anti-glare effect; when the haze is greater than 15%, the display screen will be white as a whole, while reducing clarity and brightness.
[0023] The main anti-glare particles in the anti-glare hard film provided by the present invention are micron-sized inorganic silica particles, which mainly provide haze and anti-glare effects. The haze of the hard film can be controlled according to the amount of addition. When the amount of addition is too small, the haze is low, the anti-glare function is poor, but the glossiness is high; when the amount of addition is too large, the haze is high, the anti-glare function is good, but the glossiness is reduced.
[0024] The auxiliary anti-glare particles in the anti-glare hard film provided by the present invention are nano-scale inorganic silica particles, which mainly provide the function of improving clarity. Appropriate addition can adhere to the surface of micron-scale silica, reduce the gap between micron-scale silica particles, and then reduce the flash point, improve the clarity of the anti-glare film, and make the appearance of the anti-glare film more refined. However, excessive addition will cause the nano-scale silica particles to be excessively enriched on the surface of the micron-scale silica particles, resulting in the overall appearance of the anti-glare hard film being affected.
[0025] The hardening particles in the anti-glare hardened film provided by the present invention are solvent-based inorganic nano-aluminum oxide particles, which can be evenly dispersed in the hardening liquid without self-agglomeration, and mainly provide the effect of increasing wear resistance. Appropriate addition will not only not affect the overall appearance and haze of the anti-glare film, but also can enhance the wear resistance of the anti-glare hardened film and increase the hardness of the coating to a certain extent. However, since the product is expensive, excessive addition will increase the overall cost of the hardened film.
[0026] By rationally designing the ratio of high-functional acrylate oligomers and acrylate monomers, a hardened layer with high cross-linking density, excellent hardness and wear resistance can be obtained.
[0027] Preferably, the method for modifying the silicon dioxide particles comprises the following steps:
[0028] (1) Mix the silane coupling agent, deionized water and ethanol in a mass ratio of 1:1 to 10:60 to 90, adjust the pH value to a weak acid solution, and let it stand for use;
[0029] In this treatment step, the three methoxy groups (-CH3O) in the silane coupling agent KH570 (γ-methacryloxypropyltrimethoxysilane) will undergo hydrolysis reaction with deionized water to become silanol groups (-Si-OH) and by-product methanol. The specific reaction formula is:
[0030]
[0031] This reaction is a reversible reaction, where R1 represents the organic group in the coupling agent. For this reaction process, a weakly acidic pH value is conducive to the hydrolysis of KH570, and the degree of hydrolysis of KH570 will first increase and then decrease with the increase of its addition amount. This is because the excessive silanol groups in the generated product that are not consumed in time undergo condensation polymerization, affecting the hydrolysis effect. After adding low-level fatty alcohols, such as anhydrous ethanol, to the solution system, the degree of forward hydrolysis of the silane coupling agent can be effectively controlled;
[0032] (2) The silica particles and n-butanol are prepared into a silica dispersion in a mass ratio of 1:15-30; during the preparation process, ultrasonic dispersion is first used for 15-30 minutes, and then magnetic stirring is performed for 1-2 hours to ensure that the silica particles are completely wetted by n-butanol to prepare a uniformly dispersed silica-n-butanol dispersion. The use of a high-boiling-point intermediate fatty alcohol, n-butanol, in the wetting and dispersion process of the silica particles is conducive to the subsequent grafting modification process being carried out at a higher temperature.
[0033] (3) The weak acid solution of step (1) and the silicon dioxide dispersion of step (2) are mixed in a flask at a mass ratio of 5 to 8:66 to 100 and stirred thoroughly to make them uniformly mixed, and then heated to control the reaction temperature to 80 to 100° C. and react for 1.5 to 3.5 hours. The specific reaction formula is:
[0034] R1-Si-(OH)3+R2-Si-OH→R1-Si-(OH)2-O-Si-R2+H2O
[0035] In this reaction, R2 represents other chemical bonds on the surface of silica. The hydrolyzed silanol (-Si-OH) of the silane coupling agent in process 1 will undergo polycondensation with the silanol (-Si-OH) on the surface of silica to form new silicon oxygen bonds (-Si-O-Si-), thereby completing the grafting reaction of the silane coupling agent on the surface of silica. The mass ratio of m(KH570):m(silica particles) needs to be controlled between 5% and 12%. Too little silane coupling agent will not achieve the grafting effect, and too much will easily cause the silica particles to agglomerate. The reaction temperature should be controlled at 80-100°C. The higher the temperature, the more silanols on the surface of silica particles will participate in the reaction. However, temperatures above 100°C will cause the coupling agent itself to agglomerate or decompose, affecting the grafting efficiency.
[0036] After the reaction is completed, the mixture is filtered and washed with anhydrous ethanol for several times to remove the ungrafted coupling agent. The filter cake is placed in a vacuum drying oven and dried at 60-90° C. to obtain modified silica particles, which are then ground into powder for subsequent use.
[0037] Both micron-sized silica particles and nano-sized silica particles are modified by the above method.
[0038] Preferably, the acrylate oligomer comprises 20.0% to 27.3% by weight of a ten-functional aliphatic urethane acrylate oligomer and 10.4% to 14.2% by weight of a nine-functional aliphatic urethane acrylate oligomer;
[0039] The acrylate monomer is dipentaerythritol hexaacrylate.
[0040] The ten-functional aliphatic polyurethane acrylate oligomer has more reactive functional groups, high cross-linking density, high hardness, and small shrinkage after curing. It mainly provides high hardness in the coating; the nine-functional aliphatic polyurethane acrylate oligomer has the characteristics of fast curing and good scratch resistance and wear resistance. It mainly provides high wear resistance in the coating; the six-functional acrylate monomer is DPHA (dipentaerythritol hexaacrylate), which has extremely high reactivity as an active monomer and can quickly cross-link and branch with high-functional oligomers, effectively improving the curing speed of the coating system.
[0041] Preferably, the leveling agent is BYK-355, the main chemical composition of which is a polyacrylate solution, which can improve the long-wave effect and improve the leveling and gloss of the coating; the dispersing agent is BYK-2013, the main chemical composition of which is a structured copolymer containing pigment-affinity groups, which has a good viscosity-reducing effect on silicon dioxide and can improve the color strength and transparency of the coating.
[0042] Preferably, the photoinitiator is one or more combinations thereof including 2-hydroxy-2-methyl-1-phenyl ketone (1173), 1-hydroxycyclohexyl-phenyl ketone (184), 2-methyl-1-{(4-methylthio)phenyl}-2-morpholinyl-1-propanone (907), di(2,4,6-trimethylbenzoyl)-phenylphosphine oxide (819), 2-benzyl-2-dimethylamino-1-(4-morpholinylphenyl)-1-butanone (369), etc.
[0043] Preferably, the adhesive layer includes 22.4% of ten-functional aliphatic polyurethane acrylate oligomer, 11.7% of nine-functional aliphatic polyurethane acrylate oligomer, 5.2% of hexafunctional acrylate monomer, 2.5% of photoinitiator, 1.5% of leveling agent, 0.8% of dispersion aid, 2.4% of main anti-glare particles, 0.2% of auxiliary anti-glare particles, 20.7% of hardening particles, and 32.6% of organic solvent including butyl acetate and propylene glycol methyl ether (weight ratio 1:1).
[0044] The technical solution adopted by the present invention to solve the second technical problem is: a method for preparing the anti-glare hard film for the surface of a display screen, characterized in that it comprises the following steps:
[0045] (1) adding the components of the adhesive layer into a reaction container according to proportion and mixing them evenly to form a coating;
[0046] (2) Coating the coating on the substrate layer (the coating method can be the existing microplate concave roller method or other methods), and after drying and curing, the anti-glare hard film is obtained. The thickness of the adhesive layer is preferably 2 to 4 μm, more preferably 3 μm.
[0047] The substrate layer is a transparent material, selected from one of PET (polyethylene terephthalate), TAC (triacetyl cellulose), PI (polyimide), PEN (polyethylene naphthalate), PMMA (polymethyl methacrylate), PC (polycarbonate), etc., preferably a TAC substrate with high transmittance performance, and the thickness of the TAC substrate is preferably 60 to 100 μm.
[0048] The drying and curing in the above step (2) can be carried out by infrared baking and then UV curing. The infrared baking temperature is 60-85°C, the baking time is 1-5 minutes, and the UV curing energy is 200-500 mJ / cm 2 , UV curing light intensity is 200~300mW / cm 2 .
[0049] The technical solution adopted by the present invention to solve the third technical problem is: an application of the above-mentioned anti-glare hard film for the surface of a display screen, characterized in that: the protective film is used for a vehicle-mounted display screen.
[0050] Compared with the prior art, the advantages of the present invention are as follows: 1. The anti-glare hardened film provided by the present invention adopts micron-sized silica to provide haze and anti-glare effects, and nano-sized silica fills the gaps between micron-sized silica particles to reduce the gaps between micron-sized particles, thereby effectively reducing the flash point and improving the clarity of the final product. The solvent-based nano-sized alumina particles serve as surface performance enhancing particles to provide excellent hardness and wear resistance for the thin coating.
[0051] During the preparation process, a large number of residual bonds and hydroxyl groups in different bonding states are inevitably introduced to the surface of micron / nano silica particles, which makes them have a higher surface energy in practical applications, resulting in easy agglomeration between particles and difficult dispersion. Therefore, in the actual use of micron / nano silica, the particles need to be modified and pre-treated. Therefore, the present invention uses KH570 to graft-modify the micro / nano silica particles. The silane coupling agent KH570 and the micro / nano silica form chemical bonds with each other through grafting modification, so that there is a large steric hindrance on the surface of the modified particles, which effectively reduces the agglomeration between the particles themselves. When the particles are dispersed in the coating system, because the organic long-chain molecules grafted on the modified particles themselves are not easy to agglomerate, and a certain physical entanglement or chemical cross-linking will occur with the long-chain molecules of the acrylate oligomer in the coating, the particles have better dispersibility and stability in the coating, thereby improving the fineness of the appearance of the hard film surface.
[0052] 2. The anti-glare hardened film provided by the present invention has obvious cost advantages and a simple manufacturing process. The prepared anti-glare hardened layer has high hardness and high wear resistance on the substrate and can provide a high-definition film surface appearance effect. DETAILED DESCRIPTION
[0053] The present invention is further described in detail below in conjunction with specific embodiments.
[0054] The anti-glare hard film for display screen surface of the present invention is mainly used for vehicle-mounted display screen, comprising a substrate layer and a glue layer coated on the substrate layer, wherein the glue layer comprises the following components:
[0055] Acrylate oligomer 30.4-41.5%;
[0056] Acrylate monomer 4.6-6.3%;
[0057] Photoinitiator 2.0-3.0%;
[0058] Leveling agent 1.0~2.0%;
[0059] Dispersing aid 0.5-1.0%;
[0060] Main anti-glare particles 1.2% to 3.6%;
[0061] Auxiliary anti-glare particles 0.2-0.4%;
[0062] Hardened particles 10.4-31.1%;
[0063] Organic solvent 26.8~44.8%;
[0064] The contents of the above components are in percentage by weight.
[0065] The main anti-glare particles are micron-sized silicon dioxide particles modified by a silane coupling agent, the auxiliary anti-glare particles are nano-sized silicon dioxide particles modified by a silane coupling agent, and the hardening particles are nano-sized aluminum oxide particles.
[0066] The silicon dioxide particles of the main anti-glare particles and the auxiliary anti-glare particles were purchased from Fuji Silicon Chemical Co., Ltd., Japan, and the hardened particles were purchased from Nissan Chemical Co., Ltd., Japan. The average particle size of the main anti-glare particles is D50 = 1.5 μm; the average particle size of the auxiliary anti-glare particles is D50 = 115 nm; the hardened particles are solvent-based nano-scale inorganic aluminum oxide particles, with an average particle size of D50 = 15 nm, and the above average particle size is measured by dynamic light scattering (DLS) when dispersed in a solution.
[0067] The modification method of silicon dioxide particles comprises the following steps:
[0068] (1) KH570 silane coupling agent (γ-methacryloxypropyltrimethoxysilane, purchased from Shin-Etsu Chemical Co., Ltd., Japan), deionized water and ethanol were mixed evenly in a mass ratio of 1:5:74, and the pH value was adjusted to a weak acid solution (between 4.0 and 6.5) using glacial acetic acid and sodium hydroxide, and the mixture was allowed to stand for 1 to 3 hours for use;
[0069] (2) preparing a silica dispersion by mixing silica particles and n-butanol in a mass ratio of 1:25, firstly using ultrasonic dispersion for 15 to 30 minutes, and then magnetically stirring for 1 to 2 hours to ensure that the silica particles are completely infiltrated by n-butanol, and preparing a uniformly dispersed silica-n-butanol dispersion;
[0070] (3) The weak acid solution of step (1) and the silicon dioxide dispersion of step (2) are mixed in a flask at a mass ratio of 6:85 and stirred thoroughly to make them uniformly mixed. The mixture is heated in a constant temperature oil bath to control the reaction temperature to 80° C. and reacted for 3 h. After the reaction is completed, the mixture is filtered and washed with anhydrous ethanol for 3 times. The filter cake is dried at 70° C. and then ground into powder for subsequent use.
[0071] The modification methods of the silicon dioxide particles of the main anti-glare particles and the auxiliary anti-glare particles of this embodiment all adopt the above-mentioned method.
[0072] In the following examples and comparative examples, the leveling agent is BYK-355, the dispersing agent is BYK-2013, and the photoinitiator includes 1-hydroxycyclohexyl-phenyl ketone (184) and 2-methyl-1-{(4-methylthio)phenyl}-2-morpholinyl-1-propanone (907) (the mass ratio of the two is 1:1).
[0073] The preparation methods of the anti-glare hard films of the following embodiments and comparative examples are as follows:
[0074] (1) adding the components of the adhesive layer into a reaction container according to proportion and mixing them evenly to form a coating;
[0075] (2) The coating is coated on a 60 μm thick TAC substrate layer (the coating method can be the existing wire rod roller coating method or other methods), and baked in an 80°C forced air drying oven for 3 minutes. After the coating surface is completely dry, UV curing is performed to obtain an anti-glare hard film with a coating dry film thickness of 2 to 4 μm, that is, the anti-glare hard film is obtained.
[0076] The components and contents of the adhesive layers of the embodiments and comparative examples are described in detail below:
[0077] Example 1
[0078] The glue layer includes the following components in percentage by weight:
[0079] 22.4% of ten-functional aliphatic polyurethane acrylate oligomer (Guangzhou Runao Chemical), 11.7% of nine-functional aliphatic polyurethane acrylate oligomer (Sartomer, USA), 5.2% of hexafunctional acrylate monomer (Sartomer, USA), 2.5% of photoinitiator (Aigenmon, Netherlands), 1.5% of leveling agent (BYK, Germany), 0.8% of dispersion agent (BYK, Germany), 2.4% of main anti-glare particles (Fuji Silicon Chemical Co., Ltd., Japan), 0.2% of auxiliary anti-glare particles (Fuji Silicon Chemical Co., Ltd., Japan), 20.7% of hardening particles (Nissan Chemical Co., Ltd., Japan), 32.6% of organic solvents butyl acetate and propylene glycol methyl ether (the weight ratio of butyl acetate and propylene glycol methyl ether is 1:1, the same below).
[0080] The companies in brackets of each material refer to the purchasing companies of the materials, and the same applies below.
[0081] Example 2
[0082] The glue layer includes the following components in percentage by weight:
[0083] 22.1% of ten-functional aliphatic polyurethane acrylate oligomer (Guangzhou Runao Chemical), 11.6% of nine-functional aliphatic polyurethane acrylate oligomer (Sartomer, USA), 5.1% of hexafunctional acrylate monomer (Sartomer, USA), 2.5% of photoinitiator (Aigenmon, the Netherlands), 1.5% of leveling agent (BYK, Germany), 0.8% of dispersing agent (BYK, Germany), 3.6% of main anti-glare particles (Fuji Silicon Chemical Co., Ltd., Japan), 0.2% of auxiliary anti-glare particles (Fuji Silicon Chemical Co., Ltd., Japan), 20.4% of hardening particles (Nissan Chemical Co., Ltd., Japan), 32.2% of organic solvents butyl acetate and propylene glycol methyl ether (1:1).
[0084] Example 3
[0085] The glue layer includes the following components in percentage by weight:
[0086] 22.7% of ten-functional aliphatic polyurethane acrylate oligomer (Guangzhou Runao Chemical), 11.8% of nine-functional aliphatic polyurethane acrylate oligomer (Sartomer, USA), 5.3% of hexafunctional acrylate monomer (Sartomer, USA), 2.5% of photoinitiator (Aigenmon, the Netherlands), 1.5% of leveling agent (BYK, Germany), 0.8% of dispersing agent (BYK, Germany), 1.2% of main anti-glare particles (Fuji Silicon Chemical Co., Ltd., Japan), 0.2% of auxiliary anti-glare particles (Fuji Silicon Chemical Co., Ltd., Japan), 21.0% of hardening particles (Nissan Chemical Co., Ltd., Japan), 33.0% of organic solvents butyl acetate and propylene glycol methyl ether (1:1).
[0087] Example 4
[0088] The glue layer includes the following components in percentage by weight:
[0089] 24.8% of ten-functional aliphatic polyurethane acrylate oligomer (Guangzhou Runao Chemical), 13.0% of nine-functional aliphatic polyurethane acrylate oligomer (Sartomer, USA), 5.8% of hexafunctional acrylate monomer (Sartomer, USA), 2.5% of photoinitiator (Aigenmon, the Netherlands), 1.5% of leveling agent (BYK, Germany), 0.8% of dispersion agent (BYK, Germany), 2.4% of main anti-glare particles (Fuji Silicon Chemical Co., Ltd., Japan), 0.2% of auxiliary anti-glare particles (Fuji Silicon Chemical Co., Ltd., Japan), 10.4% of hardening particles (Nissan Chemical Co., Ltd., Japan), 38.6% of organic solvents butyl acetate and propylene glycol methyl ether (1:1).
[0090] Example 5
[0091] The glue layer includes the following components in percentage by weight:
[0092] 20.0% of ten-functional aliphatic polyurethane acrylate oligomer (Guangzhou Runao Chemical), 10.4% of nine-functional aliphatic polyurethane acrylate oligomer (Sartomer, USA), 4.6% of hexafunctional acrylate monomer (Sartomer, USA), 2.5% of photoinitiator (Aigenmon, the Netherlands), 1.5% of leveling agent (BYK, Germany), 0.8% of dispersing agent (BYK, Germany), 2.1% of main anti-glare particles (Fuji Silicon Chemical Co., Ltd., Japan), 0.2% of auxiliary anti-glare particles (Fuji Silicon Chemical Co., Ltd., Japan), 31.1% of hardening particles (Nissan Chemical Co., Ltd., Japan), 26.8% of organic solvents butyl acetate and propylene glycol methyl ether (1:1).
[0093] Example 6
[0094] The glue layer includes the following components in percentage by weight:
[0095] 22.3% of ten-functional aliphatic polyurethane acrylate oligomer (Guangzhou Runao Chemical), 11.8% of nine-functional aliphatic polyurethane acrylate oligomer (Sartomer, USA), 5.2% of hexafunctional acrylate monomer (Sartomer, USA), 2.5% of photoinitiator (Aigenmon, the Netherlands), 1.5% of leveling agent (BYK, Germany), 0.8% of dispersing agent (BYK, Germany), 2.4% of main anti-glare particles (Fuji Silicon Chemical Co., Ltd., Japan), 0.4% of auxiliary anti-glare particles (Fuji Silicon Chemical Co., Ltd., Japan), 20.7% of hardening particles (Nissan Chemical Co., Ltd., Japan), 32.4% of organic solvents butyl acetate and propylene glycol methyl ether (1:1).
[0096] Example 7
[0097] The glue layer includes the following components in percentage by weight:
[0098] 22.4% of ten-functional aliphatic polyurethane acrylate oligomer (Guangzhou Runao Chemical), 11.7% of nine-functional aliphatic polyurethane acrylate oligomer (Sartomer, USA), 5.2% of hexafunctional acrylate monomer (Sartomer, USA), 2.5% of photoinitiator (Aigenmon, the Netherlands), 1.5% of leveling agent (BYK, Germany), 0.8% of dispersing agent (BYK, Germany), 2.4% of main anti-glare particles (Fuji Silicon Chemical Co., Ltd., Japan), 0.2% of auxiliary anti-glare particles (Fuji Silicon Chemical Co., Ltd., Japan), 20.7% of hardening particles (Nissan Chemical Co., Ltd., Japan), 32.6% of organic solvents butyl acetate and propylene glycol methyl ether (1:1).
[0099] Example 8
[0100] The glue layer includes the following components in percentage by weight:
[0101] 22.4% of ten-functional aliphatic polyurethane acrylate oligomer (Guangzhou Runao Chemical), 11.7% of nine-functional aliphatic polyurethane acrylate oligomer (Sartomer, USA), 5.2% of hexafunctional acrylate monomer (Sartomer, USA), 2.5% of photoinitiator (Aigenmon, the Netherlands), 1.5% of leveling agent (BYK, Germany), 0.8% of dispersing agent (BYK, Germany), 2.4% of main anti-glare particles (Fuji Silicon Chemical Co., Ltd., Japan), 0.2% of auxiliary anti-glare particles (Fuji Silicon Chemical Co., Ltd., Japan), 20.7% of hardening particles (Nissan Chemical Co., Ltd., Japan), 32.6% of organic solvents butyl acetate and propylene glycol methyl ether (1:1).
[0102] Comparative Example 1
[0103] The glue layer includes the following components in percentage by weight:
[0104] 22.5% of ten-functional aliphatic polyurethane acrylate oligomer (Guangzhou Runao Chemical), 11.7% of nine-functional aliphatic polyurethane acrylate oligomer (Sartomer, USA), 5.2% of hexafunctional acrylate monomer (Sartomer, USA), 2.5% of photoinitiator (Aigenmon, Netherlands), 1.5% of leveling agent (BYK, Germany), 0.8% of dispersing agent (BYK, Germany), 2.4% of main anti-glare particles (Fuji Silicon Chemical Co., Ltd., Japan), 20.7% of hardened particles (Nissan Chemical Co., Ltd., Japan), 32.7% of organic solvents butyl acetate and propylene glycol methyl ether (1:1).
[0105] Comparative Example 2
[0106] The glue layer includes the following components in percentage by weight:
[0107] 23.0% of ten-functional aliphatic polyurethane acrylate oligomer (Guangzhou Runao Chemical), 12.0% of nine-functional aliphatic polyurethane acrylate oligomer (Sartomer, USA), 5.3% of hexafunctional acrylate monomer (Sartomer, USA), 2.5% of photoinitiator (Aigenmon, Netherlands), 1.5% of leveling agent (BYK, Germany), 0.8% of dispersing agent (BYK, Germany), 0.2% of auxiliary anti-glare particles (Fuji Silicon Chemical Co., Ltd., Japan), 21.2% of hardening particles (Nissan Chemical Co., Ltd., Japan), 33.5% of organic solvents butyl acetate and propylene glycol methyl ether (1:1).
[0108] Comparative Example 3
[0109] The glue layer includes the following components in percentage by weight:
[0110] 27.3% of ten-functional aliphatic polyurethane acrylate oligomer (Guangzhou Runao Chemical), 14.2% of nine-functional aliphatic polyurethane acrylate oligomer (Sartomer, USA), 6.3% of hexafunctional acrylate monomer (Sartomer, USA), 2.5% of photoinitiator (Aigenmon, Netherlands), 1.5% of leveling agent (BYK, Germany), 0.8% of dispersing agent (BYK, Germany), 2.4% of main anti-glare particles (Fuji Silicon Chemical Co., Ltd., Japan), 0.2% of auxiliary anti-glare particles (Fuji Silicon Chemical Co., Ltd., Japan), 44.8% of organic solvents butyl acetate and propylene glycol methyl ether (1:1).
[0111] The main properties of the anti-glare hardened films provided in the embodiments and comparative examples of the present invention are tested using the following test methods / equipment and standards.
[0112] (1) Full light transmittance: The instrument used is Japanese Murakami Color Haze Meter, using D65 light source and testing standard JISK7361;
[0113] (2) Coating haze: The test equipment used is Japanese Murakami Color Haze Meter, using D65 light source and testing standard JIS K7136;
[0114] (3) Thickness: Use Japanese Nikon altimeter display, the test error is 0.001mm;
[0115] (4) Pencil hardness: Use a handheld pencil hardness tester with a load of 750g and Mitsubishi special hardness test pencils. The test standard is JIS K5600.
[0116] (5) Scratch resistance: The wear resistance test was conducted using an American TABER abrasion tester and Japanese TOKYUHANDS steel wool #0000 for 10 cycles back and forth. The diameter of the friction head was R = 10 mm. The wear resistance of the hardened film was determined by detecting whether there were scratches on the surface of the diaphragm.
[0117] (6) Gloss: Use the SUGA multi-angle gloss meter, test angle 60°, test standard JIS Z8741;
[0118] (7) Adhesion: The adhesion performance of the hard film is determined by using the 100-grid method and 3M 600 test tape to detect whether the coating on the film surface has fallen off;
[0119] (8) Clarity: The equipment used is a Xinjia imaging tester, with a minimum photomask width of 0.125 mm.
[0120] Schedule
[0121]
[0122]
[0123] In the above table, the decafunctional oligomer refers to a decafunctional aliphatic urethane acrylate oligomer, the nonafunctional oligomer refers to a nonafunctional aliphatic urethane acrylate oligomer, and the hexafunctional monomer refers to a hexafunctional acrylate monomer.
[0124] From the data in the table, it can be seen that by comparing Examples 1, 2, 3 and Comparative Example 2, it can be seen that the micron-sized main anti-glare particles play a major role in the haze and anti-glare effect of the anti-glare hard film. This is because the micron-sized silica particles exposed outside the coating can reduce the mirror reflection ratio of the reflected light and increase the diffuse reflection ratio; by comparing Examples 1, 4, 5 and Comparative Example 3, it can be seen that the hardened particles play a major role in the hardness and wear resistance of the hardened film. The addition of nano-sized aluminum oxide particles can significantly improve the surface strength of the hardened film, but excessive addition will not only fail to significantly improve the performance, but also lead to a rapid increase in material costs. ; By comparing Examples 1 and 6 with Comparative Example 1, it can be seen that the nano-scale auxiliary anti-glare particles play a major role in improving the clarity of the anti-glare hard film. Adding an appropriate amount of nano-scale silica particles can reduce the gaps between the micron-sized silica particles, thereby reducing the flash point of the anti-glare hard film and improving its fineness. However, excessive addition will cause the nano-scale silica particles to aggregate on the surface of the micron-sized silica particles, resulting in a deterioration in the appearance of the film surface; by comparing Examples 1, 7 and 8, it can be seen that changes in the thickness of the anti-glare hard film coating will change the degree of exposure of the surface silica particles, thereby affecting the performance parameters of the entire hard film.
[0125] The anti-glare hard film provided by the present invention adopts inorganic silicon dioxide particles of two particle sizes as composite anti-glare particles, the particles have good compatibility with the resin, the degree of particle agglomeration is low, and the coating has a more delicate appearance; in addition, nano-scale inorganic aluminum oxide particles are added to enhance the surface strength of the coating, so that the entire hard film coating still exhibits high surface hardness and abrasion resistance when the dry film thickness is only 2 to 4 μm.
[0126] The anti-glare hardened film provided by the present invention has high hardness, high wear resistance and high definition at a relatively thin coating thickness, adopts a wet coating process, and has a relatively low cost.
[0127] The above is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention. All equivalent changes and modifications made based on the content of the present invention are included in the patent scope of the present invention.
Claims
1. An anti-glare hard film for a display screen surface, comprising a substrate layer and a glue layer coated on the substrate layer, characterized in that: The glue layer comprises the following components: Acrylate oligomer 30.4-41.5%; Acrylate monomer 4.6-6.3%; Photoinitiator 2.0-3.0%; Leveling agent 1.0~2.0%; Dispersing agent 0.5-1.0%; Main anti-glare particles 1.2% to 3.6%; Auxiliary anti-glare particles 0.2-0.4%; Hardened particles 10.4-31.1%; Organic solvent 26.8~44.8%; The contents of the above components are in percentage by weight; The main anti-glare particles are micron-sized silicon dioxide particles modified by a silane coupling agent, the auxiliary anti-glare particles are nano-sized silicon dioxide particles modified by a silane coupling agent, and the hardening particles are nano-sized aluminum oxide particles.
2. The anti-glare hard film according to claim 1, characterized in that: The average particle size of the main anti-glare particles is 1.3 to 2.9 μm, the average particle size of the auxiliary anti-glare particles is 85 to 140 nm, and the average particle size of the hardening particles is 5 to 20 nm.
3. The anti-glare hard film according to claim 1, characterized in that: The modification method of the silicon dioxide particles comprises the following steps: (1) Mix the silane coupling agent, deionized water and ethanol in a mass ratio of 1:1 to 10:60 to 90, adjust the pH value to a weak acid solution, and let it stand for use; (2) preparing a silica dispersion by mixing silica particles and n-butanol in a mass ratio of 1:15 to 30; (3) mixing the weak acid solution of step (1) and the silicon dioxide dispersion of step (2) in a flask at a mass ratio of 5 to 8:66 to 100 and stirring them thoroughly to make them uniformly mixed, then heating, controlling the reaction temperature to 80 to 100° C., reacting for 1.5 to 3.5 hours, and after the reaction is completed, filtering, washing with anhydrous ethanol for multiple times, drying, and then grinding into powder for subsequent use; Both micron-sized silica particles and nano-sized silica particles are modified by the above method.
4. The anti-glare hard film according to claim 1, characterized in that: The acrylate oligomer includes 20.0% to 27.3% by weight of a ten-functional aliphatic polyurethane acrylate oligomer and 10.4% to 14.2% by weight of a nine-functional aliphatic polyurethane acrylate oligomer; The acrylate monomer is dipentaerythritol hexaacrylate.
5. The anti-glare hard film according to claim 1, characterized in that: The leveling agent is BYK-355, and the dispersing agent is BYK-2013.
6. The anti-glare hard film according to claim 1, characterized in that: The photoinitiator is one or more combinations of 2-hydroxy-2-methyl-1-phenyl ketone, 1-hydroxycyclohexyl-phenyl ketone, 2-methyl-1-{(4-methylthio)phenyl}-2-morpholinyl-1-propanone, di(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, and 2-benzyl-2-dimethylamino-1-(4-morpholinylphenyl)-1-butanone.
7. The anti-glare hard film according to claim 1, characterized in that: The invention comprises the following components in percentage by weight: 22.4% of ten-functional aliphatic polyurethane acrylate oligomer, 11.7% of nine-functional aliphatic polyurethane acrylate oligomer, 5.2% of six-functional acrylate monomer, 2.5% of photoinitiator, 1.5% of leveling agent, 0.8% of dispersion agent, 2.4% of main anti-glare particles, 0.2% of auxiliary anti-glare particles, 20.7% of hardening particles and 32.6% of organic solvent, wherein the organic solvent comprises butyl acetate and propylene glycol methyl ether in a weight ratio of 1:
1.
8. A method for preparing an anti-glare hard film for a display screen surface according to any one of claims 1 to 7, characterized in that: The steps include: (1) adding the components of the adhesive layer into a reaction container and mixing them evenly to form a coating; (2) The coating is applied on the substrate layer, and after drying and curing, the anti-glare hard film is obtained.
9. An application of the anti-glare hard film for display screen surface according to any one of claims 1 to 7, characterized in that: This anti-glare hard film is used for car displays.
Citation Information
Patent Citations
Anti-dazzle acrylic sticker
CN103740294A
Anti-dazzle coating and anti-dazzle hardening film
CN104817951A
Non-glare coating and non-glare membrane
CN105566963A
High-hardness anti-dazzle film and preparation method thereof
CN116410508A
Anti-glare film, polarizing plate and display device using the same
KR1020120024211A
Cited By
High-hardness and high-toughness polarizing composite film as well as preparation method, production system and application thereof
CN121624073A